Solidarity in Europe Citizens' Responses in Times of Crisis - Lahusen, Christian; Grasso, Maria T. (Palgrave Studies in European Political Sociology, 2018)
solidarity in Europe; transnational solidarity; political sociology; citizen responses to crisis; asylum policies; refugee crisis; attitudes towards European Union